A Counseling on Balanced Nutrition and Clean and Healthy Lifestyle for pregnant women in Bonto Biraeng Hamlet, Kec. Marusu Kab. Maros - Rate, Suherman; Yusuf, Kurnia; Nurcahyani, Icha Dian (Politeknik Negeri Madiun, 2022)
Abstrak Bonto Mate'ne Village is a village located in the Marusu District, Maros Regency, South Sulawesi Province where there are pregnant women who experience nutritional problems during pregnancy such as Chronic Energy Deficiency (KEK). Implementation of community service activities, namely counselling on balanced nutrition and clean living behaviour for pregnant women. The output of implementing community service is to provide understanding to the community, especially pregnant women about balanced nutrition and clean and healthy living behaviour so that they can apply it to their lives to reduce the risk of other health problems. The capacity for conducting outreach is limited to one hamlet with a target number of 6 people because the implementation of community service is still in a state of the Covid-19 pandemic, which is limited to a program from the government in the form of PPKM. In the results of the implementation, before the counselling on balanced nutrition, the number of respondents who understood as many as 2 people and who did not understand as many as 4 people, after the counselling the number of respondents who understood as many as 4 people and there were still 2 people who did not understand related to balanced nutrition. While before the counselling on clean and healthy living behaviour, the number of respondents who understood was 3 people and those who did not understand were 3 people, after counselling the number of respondents who understood was 5 people and there was still 1 person who did not understand related to clean and healthy living behaviour. The conclusion from community service activities, in general, went smoothly and there was a change in understanding after counselling. It is hoped that the implementation of health education in the community needs to be carried out systematically and continuously so that the community can overcome existing health problems and improve optimal health. Kata kunci: Gizi Seimbang, Perilaku Hidup Bersih, Ibu Hamil